1995
DOI: 10.1159/000188539
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline Modulates Erythrocytosis after Renal Transplantation

Abstract: Erythrocytosis occurs in 10-15% of renal transplant recipients and there is evidence that the production of erythropoietin is modulated by adenosine. We prospectively evaluated the effects of theophylline, a nonselective adenosine antagonist, in 8 patients with erythrocytosis after renal transplantation. All patients were given triple-drug immunosuppressive therapy with methylprednisolone (8 mg/daily), azathioprine (2 mg/kg b.w. daily) and cyclosporin A (4 mg/kg b.w. daily). After an 8-week course of theophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
(13 reference statements)
0
4
0
1
Order By: Relevance
“…The nonsignificant association in the KT outcomes may be because of an excellent response to treatment or good prognosis of PTE in general. As most of the patients included in our studies already received treatment and responded well to treatment with ACEI/ARB [5,67,68], phlebotomy [69], and/or theophylline [70][71][72]. The other reasons may be because of small sample size or short duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The nonsignificant association in the KT outcomes may be because of an excellent response to treatment or good prognosis of PTE in general. As most of the patients included in our studies already received treatment and responded well to treatment with ACEI/ARB [5,67,68], phlebotomy [69], and/or theophylline [70][71][72]. The other reasons may be because of small sample size or short duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Theophylline has had varied results in several studies. As described in 3 studies, theophylline has been shown to decrease Hct by 4%-15% in patients with PTE[ 61 , 62 , 64 ]. Notably, in the 2 studies cited whereby Hct after theophylline administration, one was case report ( n = 1) who discontinued theophylline after four weeks due to side effects, while the other study (Trivedi et al [ 33 ]) showed an increase in Hct that was not statistically significant[ 63 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Hemoglobin levels decreased significantly in both groups (174–149 g/L for enalapril and 171–159 g/L for losartan); however, the drop was greater (p = 0.05) with enalapril (32.6 g/L decrease) than losartan (17.0 g/L decrease). Theophylline has been found to be useful in the transplant population with dramatic absolute reductions in hematocrit of 8–12% (798,799). However, several trials have found that ACE‐Is were superior when compared directly to theophylline (800–802).…”
Section: Rationalementioning
confidence: 99%